2009
DOI: 10.1111/j.1439-0523.2009.01702.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity revealed by morphological traits and ISSR markers in hazelnut germplasm from northern Spain

Abstract: Hazelnut (Corylus avellana L.) has been a traditional crop in northern Spain. As a result of germplasm exploration over 3 years , 90 trees were selected in this region. This study describes phenotypic variation in nut and husk traits and investigates genetic relationships among selections and cultivars using inter simple sequences repeat (ISSR) markers. The local selections were phenotypically diverse and many had characteristics appreciated by the market. Eleven ISSR primers, which generated 66 polymorphic ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
28
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 26 publications
4
28
0
Order By: Relevance
“…Differentiation between Portuguese wild genotypes and landraces, and the strong relationship among the Portuguese landraces, suggest that the Portuguese landraces Ca19, Ca20, Ca21, Ca22 and Ca25 may have been derived from the introduction of a few primitive cultivars, followed by a relatively local evolution that could include crosses among them and with local wild hazelnut. The differentiation between Portuguese landraces and the group of cultivars is in agreement with the differentiation found by Ferreira et al (2010) with ISSR, Campa et al (2011) and Boccacci et al (2013) with SSR among locally cultivated accessions and a group of reference cultivars (diverse set representing the world's most important production areas). There is an agreement in the diversity analyses between the PCoAs and the hierarchical analysis, despite the relatively low proportion of total data captured in the PCoA plot.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…Differentiation between Portuguese wild genotypes and landraces, and the strong relationship among the Portuguese landraces, suggest that the Portuguese landraces Ca19, Ca20, Ca21, Ca22 and Ca25 may have been derived from the introduction of a few primitive cultivars, followed by a relatively local evolution that could include crosses among them and with local wild hazelnut. The differentiation between Portuguese landraces and the group of cultivars is in agreement with the differentiation found by Ferreira et al (2010) with ISSR, Campa et al (2011) and Boccacci et al (2013) with SSR among locally cultivated accessions and a group of reference cultivars (diverse set representing the world's most important production areas). There is an agreement in the diversity analyses between the PCoAs and the hierarchical analysis, despite the relatively low proportion of total data captured in the PCoA plot.…”
Section: Discussionsupporting
confidence: 65%
“…ISSR markers were more efficient than the AFLPs assay for polymorphism detection, as they detected 98.040 % as compared to 87.328 % for AFLPs markers. Ferreira et al (2010) found an average of six polymorphic bands per primer for the ISSRs, a lower result than the one now found for ISSRs. For AFLP, Kafkas et al (2009) found in hazelnuts a much higher mean number of polymorphic bands (29.88) than for ISSR (3.96) or RAPD (3.84).…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Nearly all efforts have been focused on cultivated forms largely to better understand their origin, to fingerprint germplasm accessions, and to evaluate genetic diversity Botta 2009, 2010;Boccacci et al 2006Boccacci et al , 2008Gökirmak et al 2009;Gürcan et al 2010). Recently, a first on-farm exploration was conducted on local ecotypes and on wild accessions in northern Spain (Asturias) by Ferreira et al (2010) and Campa et al (2011). Finally, the long history of utilization and production by humans, probably predating the Roman era (Rosengarten 1984;Bacchetta et al 2011;Boccacci and Botta 2009), makes this crop interesting from a social point of view, with a precious role in sustainable traditional agricultural systems.…”
mentioning
confidence: 99%